ANALYSIS OF CRITICAL DISCOURSE STUDY TEUN A.VAN DIJK ON THE EDITORIAL OF MEDIA INDONESIA REGARDING PERPU NO. 2/2022 - Iman Abdurohman; Agus Hamdani (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2023)
This study aims to describe the critical discourse analysis of the editorial of Media Indonesia on January 3, 2,023 with the theme